2002
DOI: 10.4049/jimmunol.169.12.7045
|View full text |Cite
|
Sign up to set email alerts
|

Differential Role of IFN-γ-Inducible Protein 10 kDa in a Cockroach Antigen-Induced Model of Allergic Airway Hyperreactivity: Systemic Versus Local Effects

Abstract: The ability of IFN-γ to antagonize established Th2 type allergic responses is well documented. To investigate the role of IFN-γ-inducible protein 10 kDa (IP10) in the allergic response, we chose to investigate the effect of IP10 neutralization on an established Th2 response. Systemic neutralization of IP10 at the time of allergen challenge increased airway hyperreactivity as well as airway eosinophil accumulation. Interestingly, IFN-γ levels were markedly reduced in both the lung and peripheral lymph node foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 43 publications
1
25
1
Order By: Relevance
“…Eosinophils highly express CCR3 and chemotax to the CCR3 ligand CCL11 (59 -62). Eosinophils have also been shown to express CXCR3 (34,63). We have shown that although CXCL10 is a sufficient chemotactic stimulus for eosinophils, CXCL9 inhibits eosinophil chemotaxis in vitro.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Eosinophils highly express CCR3 and chemotax to the CCR3 ligand CCL11 (59 -62). Eosinophils have also been shown to express CXCR3 (34,63). We have shown that although CXCL10 is a sufficient chemotactic stimulus for eosinophils, CXCL9 inhibits eosinophil chemotaxis in vitro.…”
Section: Discussionmentioning
confidence: 82%
“…However, CXCL10 transgenic mice displayed increased eosinophil accumulation, airway hyperreactivity, and IL-4 levels after OVA challenge (48). Similarly, introduction of exogenous CXCL10 into an allergic lung increased Th2-type cytokines, airway hyperreactivity, and eosinophil accumulation after allergen challenge (34). Thus, the role of CXCL10 is complex and probably depends on the location and timing of production.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The recombinant murine IP-10 and MIG antibodies and biotinylated anti-murine IP-10 and MIG antibodies used in the enzyme-linked immunosorbent assays (ELISAs) were purchased from R&D Systems (Minneapolis, MN). Polyclonal rabbit anti-murine IP-10 antibody was generated as previously described and then purified prior to use (34). Monoclonal anti-murine MIG antibody (clone 2A6.9.9) used for in vivo neutralization studies was generated as previously described (41).…”
Section: Methodsmentioning
confidence: 99%